Sistem Pendukung Keputusan Rekrutmen Pada Perusahaan Outsourcing Berbasis Web - Haryo Kusumo; Sindu Rakasiwi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Computer technology and the internet do present many conveniences in business. Includes a web-based recruitment decision support system. In the current system, PT. X received a job application file sent to the office of PT. X, after that applicants await calls from PT. X work for the interview. Such conditions make the performance of PT. X work is considered ineffective and inefficient. Therefore we need a web-based employee recruitment system that can solve this problem. The method used in the construction of this system is the analytical method hierarchy process which is carried out in several stages, namely data collection, system requirements analysis, system analysis and design, system development, and ends with testing and revision. As a result, with a web-based recruitment system, the recruitment process is effective and efficient Keywords: Recruitment, Outsourcing, Employment, Decision Support Systems